2004
DOI: 10.1016/j.jcrs.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Corneal edema and intraocular pressure after cataract surgery

Abstract: Both OVDs were beneficial in a wide range of cataract patients. However, the results suggest a tendency toward a higher complication rate with Healon5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The loss of corneal endothelium cells after intraocular surgery, especially lens surgery, may cause dysfunction and lead to corneal oedema. 4 The new central port design of the ICL V4c changes the aqueous flow, and may therefore influence corneal endothelium cells.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of corneal endothelium cells after intraocular surgery, especially lens surgery, may cause dysfunction and lead to corneal oedema. 4 The new central port design of the ICL V4c changes the aqueous flow, and may therefore influence corneal endothelium cells.…”
Section: Introductionmentioning
confidence: 99%
“…As for Healon 5 ® , randomized studies found that the postoperative IOP in Healon 5 ® -treated eyes was less than that in Viscoat ® -treated eyes at 6 hours, but was not significantly different from Viscoat ® -treated eyes at 1 day (Rainer et al 2000). Other studies found no difference in early postoperative IOP between Healon 5 ® -treated and other OVD-treated eyes (OcuCoat ® , Celoftal ® , Viscoat ® and Healon GV ® , Holzer et al 2001; Healon GV ® , Arshinoff et al 2002; Healon ® , Oshika et al 2004; Amvisc Plus ® , Moser et al 2004). No randomized studies examining the postoperative IOP increase in DisCoVisc ® – or Visthesia ® -treated eyes have been reported.…”
Section: Postoperative Complications and Ovdsmentioning
confidence: 89%
“…No blinding or incomplete blinding, but the review authors judge that the outcome is not likely to be influenced by lack of blinding; blinding of participants and key study personnel ensured, and unlikely that the blinding could have been broken. [3,7,8,[10][11][12][13]18,19,21,25,27,[29][30][31][32]35,36,[38][39][40][41][42][43]46,[49][50][51][52][53][54][55][56][57]59,[63][64][65][66][67]69,70,74] High risk…”
Section: Referencesmentioning
confidence: 99%
“…Based on the literature, a minimum of 500 cells/mm 2 is required to maintain corneal transparency [35,39]. Specular microscopy is used to measure these endothelial cell parameters, but it is only effective on the central 1 mm 2 of the cornea, and it cannot be used to assess all of the corneal layers in order to determine the degree of corneal edema [13,41,42,64]. Intraoperative mechanical stress can be caused by stress and thus trauma to the corneal endothelium.…”
Section: Endothelial Cell Loss (Ecl)mentioning
confidence: 99%

Corneal Edema after Cataract Surgery

Briceno-Lopez,
Burguera-Giménez,
García-Domene
et al. 2023
JCM